Acúmulo de metais traço cobre (Cu) e zinco (Zn) em viveiros de cultivo de camarão (Litopenaeus vannamei) - Lopes, Danielle Vieira (2006)
The progressive accumulation of copper and zinc in sediments of shrimp aquaculture ponds at Ceará State was quantified by analysing sediment profiles collected in ponds of different ages. The copper content in the sediments increased 52,25% in the younger ponds and 122,4% in the older ones. The zinc concentration increased 67,19% in the younger ponds and 80,66% in the older ones. The enrichment factor calculated for copper demonstrates that the natural sources are still more important than the anthropogenic sources of this metal to the environment. For zinc, the enrichment factor demonstrates that anthropogenic sources are more significant than the natural ones to the total load of this metal to the region. The temporal variability of copper and zinc concentrations in shrimp samples collected in Bahia was also analysed. The copper concentration in muscle tissue ranged from 14,7 ± 1,9 to 36,6 ± 2,9 Mg . g-1 and in the exoesqueleton from 34,2 ± 2,0 to 58,0 ± 4,6 Mg . g-1 (dry weight basis) . The zinc content in muscle tissue ranged from 59,3 ± 5,2 to 68,4 ± 3,5 and in the exoesqueleton from 29,5 ± 6,2 to 69,8 ± 12,1Mg . g-1 (dry weight basis). The values found in Bahia differ from those calculated to the lower Jaguaribe basin, demonstrating a regional character of the data.